A meta analysis of N2O emission characteristics and influencing factors in facultative composting and an estimation of emissions in China - Kaishu Luo; Ruolan Tang; Yan Liu; Yaru Shao; Guoxue Li; Jing Yuan (Environmental Research, 2026)

Two-phase removal kinetics of antimicrobial resistance in collaborative composting: Thermophilic enhancement and rebound suppression - Ruonan Ma; Xuyan Li; Ruolan Tang; Yan Liu; Jiani Wang; Guoxue Li; Si Li; Shenzhong Tian; Tao Jiang; Jiali Chang; Jing Yuan (Bioresource Technology, 2026)

Mercury pollution remediation in paddy fields with biochar amendment - Yanxin Hu; Chuan Wang; Junyao Yan; Ruolan Li; Rasheed Mohammed Abdul; Yan An; Jinjuan Li; Ping Li (Applied Geochemistry, 2026)

Multi-media antibiotics, intracellular and extracellular antibiotic resistance genes in marine protected areas of the South China Sea: Spatiotemporal distribution and multi-factor drivers of dissemination - Chengcheng Bu; Limin Ma; Yu Hua; Shaopeng Xu; Yutong Zhang; Huadong Yi; Yuchen Han; Haoyu Zeng; Yongzhi Wang; Xiaoying Xu; Qihui Zhao; Ruolan Jia; et al. (Marine Pollution Bulletin, 2026)

Spatiotemporal dynamics and spatial attribution of water conservation under land use/cover changes and the SSP2–4.5 medium-forcing scenario in the northern slope of the Tianshan Mountains - Hongjie Jia; Qin Han; Yingchao Ji; Dong Liu; Ruolan Chen; Jiangyue Li; Haoyang Du (Regional Environmental Change, 2026)

A comparative study of methods for quantifying sand-sized sediment grain textural parameters - Xiaotian Shen; Xing Jian; Wei Zhang; Ruolan Liao; Dongming Hong; Chao Li; Shaohua Zhao; James T. Liu; Yuan-Pin Chang (Sedimentary Geology, 2026)

Divergent aerosolization behaviors of bacteria and fungi shape the pathogen profile of pig manure composting-derived bioaerosols - Xia Gao; Jiani Wang; Lijuan Peng; Tianlong Song; Ruolan Tang; Yan Yang; Guoxue Li; Jing Yuan (Journal of Environmental Chemical Engineering, 2026)

Temporal pattern clustering and LightGBM-based analysis of factors influencing rural photovoltaic deployment in China - Ruolan Li; Xunhe Zhang; Erling Li (Journal of Geographical Sciences, 2026)

Porcine epidemic diarrhea virus influences the expression of tight junction proteins through the polarity protein PAR6 - Tingyu Hu; Ruolan Zhang; Qian Weng; Simin Wang; Yuheng Li; Zhihua Pei; Kai Wang; Guixue Hu (Virus Genes, 2026)

Multi–scale drift characteristics of Ulva prolifera in the Yellow Sea derived from deep learning–based MODIS and Sentinel-1 observations - Xiaomeng Geng; Huiru Li; Ruolan Fan; Yunlong Zhao; Enran Guo; Runbing Qi (Marine Pollution Bulletin, 2026)

High-intensity intermittent aeration with multi-stage descending rates enhances oxygen uptake to mitigate nitrogen emissions and promote humification in composting - Ruolan Tang; Ruonan Ma; Kaishu Luo; Yifan Zhai; Bin cui; Fanqiao Meng; Guoxue Li; Yue Xie; Jing Yuan (Journal of Cleaner Production, 2026)

Intercropping enhances aggregate stability on acidic red-soil slopes via an arbuscular mycorrhizal fungi-mediated glomalin-enzyme pathway - Ruolan Tang; Qirui Wang; Huahui Li; Xiongxing Pu; Wanting Li; Benshuai Yan; Ting Wang; Zilin Wang; Maopan Fang; Xinyue Li; Yongmei Li; Jixia Zhao (Applied Soil Ecology, 2026)

Shipwake-YOLO: Ship Wake Detection and Instance Segmentation for Visual Navigational-State Cue Extraction - Shaoxi Li; Xingchen Ji; Chuankao Yang; Ruolan Zhang (Journal of Marine Science and Engineering, 2026)
Visual perception is an important component of close-range maritime situational awareness, particularly when conventional sources such as AIS and radar are delayed, incomplete, or unavailable. Ship wakes provide motion-related visual cues, but their segmentation remains difficult because wake regions are elongated, weakly textured, and frequently mixed with water-surface clutter. This study develops Shipwake-YOLO, a wake-oriented adaptation of YOLOv9-Seg for ship and wake instance segmentation in inland-waterway images. The task is formulated as visual navigational-state cue extraction rather than validated future manoeuvre prediction. The model segments hull and wake instances and provides mask-derived spatial cues for possible downstream state interpretation. The architecture introduces iAFF into cross-scale feature fusion, adapts the high-level SPPELAN aggregation block with SAConv-enhanced convolution, replaces selected downsampling paths with iSACADown, and adopts MPD-IoU as the bounding-box regression loss. On a 2100-image dataset collected from the Wuhu Channel of the Yangtze River, Shipwake-YOLO improves Box-mAP@50 from 77.7% to 84.6% and Mask-mAP@50 from 67.6% to 79.8% relative to the YOLOv9-Seg baseline. Under stricter IoU thresholds, the model reaches 48.9 in Box-mAP@[0.50:0.95] and 46.2 in Mask-mAP@[0.50:0.95]. The parameter count is reduced by 7.5%, and GFLOPs decrease from 144.2 to 137.1. These results indicate that the proposed adaptation improves ship-wake perception within the collected inland-waterway setting and provides a visual basis for downstream navigational-state estimation.

Characterization and encapsulation properties of pectic polysaccharides derived from Choerospondias axillaris fruit - Hao Liu; Ruolan Du; Hongxiang Li; Wenbo Zhao; Liang Leng; Jun Lu; Haiqiang Zhang; Sanyin Zhang (Carbohydrate Polymers, 2026)

HOPO-functionalized MXene self-supporting membrane for highly efficient and selective uranium extraction from radioactive wastewater - Jiaxin Li; Yinlu Dong; Yu Wang; Xiangcao Chang; Jicui Wen; Yuhang Zhang; Wenhua Zhu; Lichan Xiao; Ruohan Guo; Chaoran Li; Zhiyun Meng; Ruolan Gu; et al. (Chemical Engineering Journal, 2026)

Co-application of organic fertilizer and biochar ameliorates the triple composite pollution of microplastics, antibiotic resistance genes, and heavy metals in soil - Zhengzhe Fan; Jiang Wu; Ruolan Li; Houyu Li; Yan Xu (Journal of Hazardous Materials, 2026)

RSAND: A Fine-Grained Dataset and Benchmark for AtoN Detection in River–Sea Intermodal and Complex Estuarine Environments - Qi Chen; Mingyang Pan; Zongying Liu; Ruolan Zhang; Fei Yan; Xiaofeng Pan; Yang Zhang; Chao Li (Journal of Marine Science and Engineering, 2026)
Robust visual perception of Aids to Navigation (AtoN) is essential for Maritime Autonomous Surface Ships (MASS) operating in restricted navigational waters, where estuarine clutter, fog, glare, and dense traffic can severely degrade detection reliability. Existing maritime vision datasets largely emphasize open-sea targets or coarse AtoN categories, leaving a granularity gap for IALA-compliant fine-grained understanding in river–sea transition and port-approach channels. The River–Sea AtoN Navigation Dataset (RSAND) is introduced, a large-scale benchmark collected along the Yangtze River Deepwater Channel from inland corridors to open estuarine waters. RSAND contains 39,926 images with expert-verified bounding-box annotations and a hierarchical taxonomy that jointly captures AtoN location, shape, and functional semantics across 29 categories. To support both realistic long-tailed evaluation and standardized model comparison, two protocols are provided: RSAND-Full (29 categories) and RSAND-Balanced (10 critical categories). All quantitative benchmarking results in this paper are reported on RSAND-Balanced, while RSAND-Full is released for future large-scale long-tailed robustness studies. Benchmarking experiments on 14 state-of-the-art detectors demonstrate that YOLOv12x achieves superior performance with an mAP50-95 of 80.7%, significantly outperforming previous baselines. However, the analysis reveals persistent challenges in detecting small, distant targets and distinguishing visually similar functional markers. RSAND and the accompanying evaluation toolkit are released to facilitate reproducible research toward safer and smarter marine and coastal navigation.

Al-doped Ti4O7 with superior oxidation resistance and optical stability for high-temperature solar-thermal applications - Peize Lyu; Wenzhao Sun; Bo Yang; Wanqi Chen; Ruolan Tang; Haile Yan; Zongbin Li; Song Li; Liang Zuo (Chemical Engineering Journal, 2026)

Exceptional methylmercury bioaccumulation in rice grain from karst region with high geological background - Langfei Wei; Shaochen Yang; Ruolan Li; Rasheed Mohammed Abdul; Yanxin Hu; Haiyu Yan; Baolin Wang; Haiyan Hu; Ping Li (Applied Geochemistry, 2026)

Effects of bedding materials and composting methods on gaseous emissions and compost quality across the whole chain of sheep husbandry and manure management - Xia Gao; Ziming Yin; Ruolan Tang; Yan Yang; Yiran Zhou; Danyang Li; Guoxue Li; Xiaoyan Gong; Jing Yuan (Waste Management, 2026)

Unraveling the role of abundant and rare species in antibiotic resistance genes migration in soil-crops system under different fertilization regimes - Dandan Zhang; Zhengzhe Fan; Qifan Yang; Ruolan Li; Houyu Li; Yan Xu (Journal of Environmental Chemical Engineering, 2025)

Atmospheric and room-temperature plasma mutagenesis enhances the tolerance of Arthrospira platensis to photoinhibition and high-CO2 levels - Ruolan Yuan; Chunli Yu; Rui Xu; Jin Liu; Lina Zhou; Shengxi Shao; Jun Qian; Jingjing Li; Peilun Xu; Wenguang Zhou (Chemical Engineering Journal, 2025)

Machine learning-driven design for globally optimal performance of flexible pressure sensors - Yuhan Zhao; Zhanfeng Guo; Zetian Zhao; Hengbin Ding; Xiaoshi Li; Yihan Xu; Daixuan Wu; Zhongheng Sun; Yifan Li; Jiaming Li; Ruolan Zhao; Minghao Wang; et al. (Chemical Engineering Journal, 2025)

Nanozyme-mediated drug ion-exchange strategy ameliorates inflammatory bowel disease by scavenging ROS and reprogramming proinflammatory macrophages - Hongyan Lu; Ying Cheng; Xiangling Pu; Xingtao Zhao; Ruolan Li; Ruiqi Sun; Xiaoman Xie; Mingyue Wu; Shuo Zhang; Qiong Pan; Jin Chai (Chemical Engineering Journal, 2025)

Defect-engineered Z-scheme BiOBr/TiO2 heterojunctions with interfacial potential wells for selective CO2 photoreduction - Shijie Liu; Ruolan Zhao; Yachao Xu; Maoxiang Li; Zihan Ma; Xin Chang; Ying Wang; Mingyi Zhang (Chemical Engineering Journal, 2025)

MicroRNA-592 suppresses breast cancer progression by targeting CYP20A1 to modulate the CHOP pathway - Ruolan Pan; Shangquan Jiang; Jinxing Su; Caiyun Zhang; Xiaoxing Li; Kan He (Journal of Physiology and Biochemistry, 2025)

Optimizing organic waste co-composting: Component ratio thresholds for dual enhancement of maturity and gaseous emission reduction - Ruonan Ma; Ruolan Tang; Guannan Zheng; Jiani Wang; Zhongliang Cui; Yan Liu; Guoxue Li; Fanqiao Meng; Jing Yuan (Journal of Environmental Chemical Engineering, 2025)

Response of maturity, humification, and gaseous emissions to initial moisture content in collaborative composting of multiple organic solid wastes - Xuyan Li; Jiacong Lin; Ruolan Tang; Yan Liu; Jiani Wang; Guoxue Li; Jing Yuan; Ruonan Ma (Journal of Environmental Chemical Engineering, 2025)

Excessive humus fertilization accelerates antibiotic resistance genes dissemination in soil: Interspecies electron transfer-mediated ecological succession as a key mechanism - Qifan Yang; Dandan Zhang; Yinuo Ding; Ruolan Li; Houyu Li; Yan Xu (Journal of Environmental Chemical Engineering, 2025)

Black phosphorus-doped Janus structured electrospun fibrous membrane with antibacterial properties for wound healing - Ruolan Du; Xinyu Li; Wenbo Wu; Jingxin Zhou; Zhiwei Liu; Yuehua Wang; Tifeng Jiao (Chemical Engineering Journal, 2025)

Water-saving irrigation suppresses on soil-crop pathogenicity: Insight on the co-host of virulence factors and antibiotic resistance genes - Lizhi Zhao; Yuhui Li; Qifan Yang; Ruolan Li; Houyu Li; Yan Xu (Journal of Hazardous Materials, 2025)

Optimization of sludge retention time for rapid start-up and stable operation of high-rate partial nitritation in a continuous flow reactor treating municipal wastewater - Ruolan Wen; Min Ye; Yanxu Liu; Chihao Lin; Yu-You Li; Jianyong Liu (Journal of Environmental Management, 2025)

The effect of probiotics supplementation on cancer-treatment complications: a critical umbrella review of interventional meta-analyses - Zhao Yang; Shijie Zhang; Lu Ying; Wenjing Zhang; Xiaoyang Chen; Youfeng Liang; Ruolan Chen; Keying Yao; Chunhui Li; Changyuan Yu; Parmida Jamilian; Meysam Zarezadeh; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Bioremediation potential of sulfadiazine-degrading bacteria: Impacts on ryegrass growth and soil functionality - Minghao Yin; Ping Li; Chengzhuang Chen; Ruolan Jia; Banghua Xia; Yiwei Liu; Aiqiu Liu; Ling Liu; Zhi-Hua Li (Journal of Hazardous Materials, 2025)

Transport and transformation of colloidal and particulate mercury in contaminated watershed - Junyao Yan; Ruolan Li; Chuan Wang; Shaochen Yang; Mingyu Shao; Leiming Zhang; Ping Li; Xinbin Feng (Water Research, 2025)

Preparation of ZnWO4/Bi4O5I2 composite photocatalyst and study of its antibacterial properties - Ling Zhang; Zixin Wang; Ruolan Wei; Tengyuan Gao; Jingmei Li; Luyin Zhao; Deming Han; Xiulong Li (Journal of Water Process Engineering, 2025)

Plant secretions and volatiles contribute to the evolution of bacterial antibiotic resistance in soil-crop system - Houyu Li; Qifan Yang; Wei Liu; Ruolan Li; Dandan Zhang; Guilong Zhang; Yan Xu (Journal of Environmental Sciences, 2025)

Iron-modified biochar enhanced nitrogen retention during composting:bridging chemisorption and microbiome modulation - Ruolan Tang; Sheng Yao; Yan Liu; Tianyu Ren; Jingyuan Ma; Xiaoyan Gong; Guoxue Li; Ruonan Ma; Jing Yuan (Chemical Engineering Journal, 2025)

Mapping cropland use changes in the Guanzhong Plain of China based on a two-level classification framework - Wei Zhang; Jianhong Liu; Ruolan Jia; Xi Wang; Xiya Yan; Ziqi Wang; Jing Wang; Wei Li; Peijun Sun (International Journal of Remote Sensing, 2025)

Exploring the effect of low-temperature thermal-alkaline pretreatment on struvite recovery from metals-phosphorus rich sludge - Lin Wei; Junjie Ji; Tianqiu Hong; Yugang Dong; Qiang Zhang; Lei Luo; Ruolan Li; Ziyue Li; Yiming Tang (Journal of Environmental Chemical Engineering, 2025)

Adaptive Temporal Reinforcement Learning for Mapping Complex Maritime Environmental State Spaces in Autonomous Ship Navigation - Ruolan Zhang; Xinyu Qin; Mingyang Pan; Shaoxi Li; Helong Shen (Journal of Marine Science and Engineering, 2025)
The autonomous decision-making model for ship navigation requires extensive interaction and trial-and-error in real, complex environments to ensure optimal decision-making performance and efficiency across various scenarios. However, existing approaches still encounter significant challenges in addressing the temporal features of state space and tackling complex dynamic collision avoidance tasks, primarily due to factors such as environmental uncertainty, the high dimensionality of the state space, and limited decision robustness. This paper proposes an adaptive temporal decision-making model based on reinforcement learning, which utilizes Long Short-Term Memory (LSTM) networks to capture temporal features of the state space. The model integrates an enhanced Proximal Policy Optimization (PPO) algorithm for efficient policy iteration optimization. Additionally, a simulation training environment is constructed, incorporating multi-factor coupled physical properties and ship dynamics equations. The environment maps variables such as wind speed, current velocity, and wave height, along with dynamic ship parameters, while considering the International Regulations for Preventing Collisions at Sea (COLREGs) in training the autonomous navigation decision-making model. Experimental results demonstrate that, compared to other neural network-based reinforcement learning methods, the proposed model excels in environmental adaptability, collision avoidance success rate, navigation stability, and trajectory optimization. The model’s decision resilience and state-space mapping align with real-world navigation scenarios, significantly improving the autonomous decision-making capability of ships in dynamic sea conditions and providing critical support for the advancement of intelligent shipping.

A chemically enhanced primary treatment and anammox-based process for sustainable municipal wastewater treatment: The advantage and application prospects - Ruolan Wen; Jiayuan Deng; Huan Yang; Yu-You Li; Hui Cheng; Jianyong Liu (Journal of Environmental Management, 2025)

Gender differences in commuting travel mode choices among young adults: A spatial heterogeneity perspective - Yang Liu; Ruolan Shen; Mingwei He; Xuefeng Li; Zhuangbin Shi (Journal of Transport Geography, 2025)

Identification and Removal of Light Pollution in Maritime Night-Time Images Based on Spatial Frequency Blocks - Hui Sun; Jingyang Wang; Mingyang Pan; Zongying Liu; Shaoxi Li; Ruolan Zhang; Yang Wei (Journal of Marine Science and Engineering, 2025)
The safety of ships during nighttime navigation has always been a major concern. With the widespread application of technologies such as intelligent recognition, intelligent detection, and unmanned ship navigation at night, nighttime maritime light pollution has significantly affected the effectiveness of these intelligent technologies and navigation safety. Therefore, effectively eliminating nighttime maritime light pollution has become an urgent challenge that needs to be addressed. This paper presents a model based on spatial frequency blocks (SFBs) to solve the problem of light pollution in nighttime sea images. The model includes ResNet-50, an encoder, a decoder, and a discriminator. To enable the model to better remove the influence of light pollution, this study designs a method of first detecting the light pollution area and then removing it. It extracts image information from the space–frequency domain to help eliminate light pollution and retain more image information. The experimental results show that on the nighttime light pollution dataset, the Peak Signal-to-Noise Ratio (PSNR) of the model is improved to 24.91 compared to the current state-of-the-art image restoration model, while the Frechet inception distance (FID) is reduced to 64.85. At the same time, in the real night environment, the model can better remove light pollution to recover the original nighttime information. It has excellent performance and provides a certain reference value for advancing the safety of nighttime maritime navigation.

Bioaerosol emission characteristics and potential risks during composting: Focus on pathogens and antimicrobial resistance - Ruonan Ma; Lijuan Peng; Ruolan Tang; Tao Jiang; Jiali Chang; Guoxue Li; Jiani Wang; Yan Yang; Jing Yuan (Journal of Hazardous Materials, 2025)

Correlation analysis and modeling application from objective indicators to subjective evaluation of scented tea: A case study of rose tea - Ruolan Song; Meng Shen; Yanran Wang; Youyi Sun; Jiamu Ma; Qingyue Deng; Xueyang Ren; Xianxian Li; Yuan Zheng; Yingyu He; Feng Zhang; Mingxia Li; et al. (Food Chemistry, 2025)

Effects of single or combined exposure to tralopyril and ocean acidification on energy metabolism response and sex development in Pacific oysters (Crassostrea gigas) - Ping Li; Minghao Yin; Xu Wang; Ruolan Jia; Chengzhaung Chen; Bin Liu; Yiwei Liu; Bianhao Zeng; Tengzhou Li; Ling Liu; Hong-Jun Song; Zhi-Hua Li (Marine Pollution Bulletin, 2024)

Phosphate, magnesium containing additives and biochar regulate compost maturity and synergistically reduce odor emission in chicken manure composting: Role of physicochemical, bacterial and fungal dynamics - Yan Liu; Ruonan Ma; Ruolan Tang; Guannan Zheng; Guoxue Li; Jie Yin; Jing Yuan (Journal of Environmental Management, 2024)

The effect of green coffee extract supplementation on obesity indices: critical umbrella review of interventional meta-analyses - Zhao Yang; Zhuo Shao; Weiyi Ouyang; Lu Ying; Rui Guo; Mingxuan Hao; Youfeng Liang; Wenjing Zhang; Xiaoyang Chen; Ruolan Chen; Changyuan Yu; Kousalya Prabahar; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Microbial nitrogen transformation regulates pathogenic virulence in soil environment - Xiujing Guan; Yan Xu; Dandan Zhang; Houyu Li; Ruolan Li; Rongguang Shi (Journal of Environmental Management, 2024)

Mercury sources, transport, and transformation in rainfall-runoff processes: Mercury isotope approach - Ruolan Li; Junyao Yan; Chuan Wang; Shaochen Yang; Lin Zhang; Tao Peng; Wei Zhu; Ping Li; Leiming Zhang; Xinbin Feng (Water Research, 2024)

Differential drivers on the occurrence of antibiotic resistance genes in agricultural soils and crops: Evidence from the different fertilization regimes - Ruolan Li; Yuhui Li; Houyu Li; Guilong Zhang; Yan Xu (Journal of Environmental Management, 2024)

Dicyandiamide addition delay nitrous oxide emission and shift its production pathway from denitrification to incomplete nitrification in maturation phase of composting - Yan Liu; Ruolan Tang; Guoliang Liu; Guoxue Li; Jiani Wang; Yu Cai; Yilin Kong; Jing Yuan (Chemical Engineering Journal, 2024)

Rapid and highly sensitive colorimetric LAMP assay and integrated device for visual detection of monkeypox virus - Yadan Peng; Ruolan Hu; Shuang Xue; Yugan He; Lili Tian; Zehan Pang; Yile He; Yuqi Dong; Yinghan Shi; Shuqi Wang; Bixia Hong; Ke Liu; et al. (Analytica Chimica Acta, 2024)

Pickering emulsion stabilized using modified gluten protein - Yongling Song; Yuanyuan Hou; Siqi Ren; Chenling Qu; Miao Li; Yanlin Tu; Ruolan Wang (Journal of Food Engineering, 2024)

Acceleration of the charge transfer rate for efficient photocatalytic hydrogen production via adjusting modulator and introducing electronic bridge dual strategies - Xingyan Liu; Haibo Zhou; Ruolan Li; Maosen Xu; Chenghua Zhang; Zhengsijia Wu; Youzhou He; Xu Zou; Min Fu; Siping Wei (Fuel, 2024)

A novel method to quantify chitosan in aqueous solutions by ultrahigh-performance liquid chromatography–tandem mass spectrometry - Ting Xue; Lei Zhou; Fanjun Wang; Zhuang Tian; Nanxi Li; Tong Ye; Ruolin Hao; Lei Yang; Ruolan Gu; Hui Gan; Zhuona Wu; Xiaoxia Zhu; et al. (Carbohydrate Polymers, 2024)

Ocean acidification alters shellfish-algae nutritional value and delivery - Ruolan Jia; Minghao Yin; Xue Feng; Chengzhuang Chen; Chunfeng Qu; Ling Liu; Ping Li; Zhi-Hua Li (Science of The Total Environment, 2024)

Response of organic aerosol in Beijing to emission reductions during the XXIV Olympic Winter Games - Qipeng Qu; Shuxiao Wang; Bin Zhao; Ruolan Hu; Chengrui Liang; Haowen Zhang; Shengyue Li; Boyang Feng; Xuan Hou; Dejia Yin; Jinhong Du; Yangxi Chu; et al. (Science of The Total Environment, 2024)

Interaction of high amylose corn starch with polyphenols: Modulating the stability of polyphenols with different structure against thermal processing - Haoran Fan; Xu Yao; Zhijun Chen; Ruolan Ma; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Food Chemistry, 2024)

Semi-dynamic spatial–temporal graph neural network for traffic state prediction in waterways - Le Li; Mingyang Pan; Zongying Liu; Hui Sun; Ruolan Zhang (Ocean Engineering, 2024)

Study on the improvement of complexation efficiency and anti-digestibility of phenolic acids based on electrospun starch fibers - Haoran Fan; Xu Yao; Zhijun Chen; Ruolan Ma; Yanhong Bi; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Food Research International, 2024)

Combined exposure of beta-cypermethrin and emamectin benzoate interferes with the HPO axis through oxidative stress, causing an imbalance of hormone homeostasis in female rats - Yuxin Li; Xianzhi He; Bin Sun; Nannan Hu; Jiamin Li; Ruolan You; Feiyan Tao; Lei Fang; Yuanyuan Li; Qingfeng Zhai (Reproductive Toxicology, 2024)

Rice bran peptide with α-glucosidase inhibition activity: Preparation, evaluation and molecular mechanism - Weiwei Liu; Ruolan Ma; Gengjie Cui; Yangyang Wen; Hongyan Li; Jing Wang; Baoguo Sun (Journal of Cereal Science, 2024)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Response Surface Methodology and Artificial Neural Network Modeling for the Removal of Volatile Organic Compounds in Biotrickling Filters - Tianqiu Hong; Lin Wei; Kangping Cui; Yugang Dong; Lei Luo; Tingting Zhang; Ruolan Li; Ziyue Li; Yiming Tang (Water, Air, & Soil Pollution, 2023)

Bradykinin-pretreated Human cardiac-specific c-kit+ Cells Enhance Exosomal miR-3059-5p and Promote Angiogenesis Against Hindlimb Ischemia in mice - Jingzhou Li; Fei Song; Ruolan Chen; Jinjuan Yang; Jie Liu; Li Huang; Fuyu Duan; Meng Kou; Boon Xuan Lian; Xiaoxia Zhou; Weimin Han; Liang Mao; et al. (Stem Cell Reviews and Reports, 2023)

Influencing Factors and Improvement Suggestions for Agricultural Green Development Performance: Empirical Insights from China - Erling Li; Mengzhen Zhang; Ruolan Li; Qingqing Deng (Chinese Geographical Science, 2023)

A global meta-analysis of greenhouse gas emissions and carbon and nitrogen losses during livestock manure composting: Influencing factors and mitigation strategies - Yan Liu; Ruolan Tang; Liqiong Li; Guannan Zheng; Jiani Wang; Guoying Wang; Ziyang Bao; Ziming Yin; Guoxue Li; Jing Yuan (Science of The Total Environment, 2023)

Temporal succession and spatial heterogeneity of humification, pathogens and bacterial community in facultative heap composting - Yan Yang; Yilin Kong; Guoying Wang; Yujun Shen; Ruolan Tang; Ziming Yin; Jia Yang; Guoxue Li; Jing Yuan (Process Safety and Environmental Protection, 2023)

Heavy metals in fish, rice, and human hair and health risk assessment in Wuhan city, central China - Muhammad Ubaid Ali; Chuan Wang; Yuan Li; Ruolan Li; Shaochen Yang; Li Ding; Lin Feng; Bo Wang; Ping Li; Ming Hung Wong (Environmental Pollution, 2023)

Revealing and quantifying the effect of cattiite coprecipitation on the purity of K-struvite in aqueous solution - Lin Wei; Tingting Zhang; Tianqiu Hong; Yugang Dong; Dongdong Ji; Lei Luo; Ruolan Li; Ziyue Li; Yiming Tang (Journal of Environmental Chemical Engineering, 2023)

Multiple Attention Mechanisms-Based Convolutional Neural Network for Desert Seismic Denoising - Juan Li; Ruolan Qu; Changgang Lu (Pure and Applied Geophysics, 2023)

Shellfish-algal systems as important components of fisheries carbon sinks: Their contribution and response to climate change - Ruolan Jia; Ping Li; Chengzhuang Chen; Ling Liu; Zhi-Hua Li (Environmental Research, 2023)

Impact of battery electric vehicles on ventilation design for road tunnels: A review - Xu Wang; Mingnian Wang; Ruolan Jiang; Jiani Xu; Bingtian Li; Xiao Wang; Mingyu Lei; Pengfei Su; Chaopeng Liu; Qianru Yang; Jianle Yu (Tunnelling and Underground Space Technology, 2023)

Molecular tracers, mass spectral tracers and oxidation of organic aerosols emitted from cooking and fossil fuel burning sources - Chengrui Liang; Shuxiao Wang; Ruolan Hu; Guanghan Huang; Jinzi Xie; Bin Zhao; Yuyang Li; Wenfei Zhu; Song Guo; Jingkun Jiang; Jiming Hao (Science of The Total Environment, 2023)

Effects of radon exposure on gut microbiota and its metabolites short-chain fatty acids in mice - Huimeng Liu; Meiyu Wang; Guangrui Chen; Huiyu Zhou; Jiahui Dong; Lei Yang; Tong Li; Zhiyun Meng; Ruolan Gu; Hui Gan; Zhuona Wu; Shuchen Liu; et al. (Toxicology, 2023)

Boosting the photocatalytic hydrogen evolution and NO removal via synergistic effects of in-situ Pt NPs formation and titanium integration in Zr-Porphyrin MOFs - Ruolan Li; Zongqian Wu; Ya Chen; Xingyan Liu; Weiwei Guo; Yumin Huang; Min Fu; Youzhou He (Fuel, 2023)

Mercury migration to surface water from remediated mine waste and impacts of rainfall in a karst area – Evidence from Hg isotopes - Junyao Yan; Ruolan Li; Muhammad Ubaid Ali; Chuan Wang; Bo Wang; Xingang Jin; Mingyu Shao; Ping Li; Leiming Zhang; Xinbin Feng (Water Research, 2023)

Effect of moisture content, aeration rate, and C/N on maturity and gaseous emissions during kitchen waste rapid composting - Ruolan Tang; Yan Liu; Ruonan Ma; Lanxia Zhang; Yanming Li; Guoxue Li; Dingmei Wang; Jiacong Lin; Qinfen Li; Jing Yuan (Journal of Environmental Management, 2023)

A novel antibacterial tyroscherin derivative with a natural unprecedented morpholine-2, 3-dione structural unit from the fungus Pseudallescheria boydii - Ruolan Chen; Ziyang Li; Chan Qin; Peijun Lu; Jiaru Lin; Wenxu Zheng; Yahong Xiong; Chunyuan Li (Natural Product Research, 2022)

The combined effect of titanium dioxide nanoparticles and cypermethrin on male reproductive toxicity in rats - Yuxin Li; Mingqing Zhong; Xianzhi He; Ruoyu Zhang; Yu Fu; Ruolan You; Feiyan Tao; Lei Fang; Yuanyuan Li; Qingfeng Zhai (Environmental Science and Pollution Research, 2022)

Neuroprotective effect of green tea extractives against oxidative stress by enhancing the survival and proliferation of PC12 cells - Zhenlu Cai; Xiaoxuan Hu; Ruolan Tan; Yunran Feng; Meiqi Sun; Ning Ma; Xingxing Li; Li Huang; Jing An; Qian Ge; Haixia Lu (Molecular & Cellular Toxicology, 2019)

miR-363-3p is activated by MYB and regulates osteoporosis pathogenesis via PTEN/PI3K/AKT signaling pathway - Mingyi Li; Ruolan Luo; Wenjian Yang; Zhen Zhou; Chenxia Li (In Vitro Cellular & Developmental Biology - Animal, 2019)

HIF-1α/Beclin1-Mediated Autophagy Is Involved in Neuroprotection Induced by Hypoxic Preconditioning - Na Lu; Xingxing Li; Ruolan Tan; Jing An; Zhenlu Cai; Xiaoxuan Hu; Feidi Wang; Haoruo Wang; Chengbiao Lu; Haixia Lu (Journal of Molecular Neuroscience, 2018)